Grupy młodzieży w wielkomiejskim środowisku. Próba typologii - Sosnowski, Adam; Walkowiak, Jerzy (Wydział Prawa i Administracji UAM, 1986)
The article presents a fragment research results of housing estate communities of Szczecin and Poznan. It concerns groups of youth (of the same age and others) in the age 13 - 20-working or studying. The authors dwell on the sociological definitions of social group providing also their own understanding of the notion. It is found that the examined youth belongs most frequently to the contemporary groups (packs and gangs) and to loose social circles. Criteria to divide the population were: 1) level of the social adjustment, 2) level of social, cultural and educational activity. These criteria allowed to distinguish „exemplary" youth, „medium", „difficult" from the social margin and „difficult" in the conflict with law. The research proves that the respective categories are loosely related to school as institution, with the example of „medium" youth. Next, the composition of youth groups and circles was established. It appeared that on account of their institutionalized background, it is mostly the „medium" youth which belongs to them, it is rarely the case of „exemplary" youth and sporadically only of the „difficult" one. Members of extraschool packs are usually the „difficult" ones (both categories), next the „exemplary" ones and rarely the „medium" ones. It has been also established that the binding force varies as well: it is common interests for the „exemplary" and „medium" ones and crime and delinquency for the „difficult" ones, it concerns mostly the youth remaining in conflict with law.
Groups of youth in the urban environment attempt at typology